2020
DOI: 10.1007/s10340-020-01205-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and fitness cost of spinosad-resistant alleles in Ceratitis capitata

Abstract: The sustainability of control programs for the Mediterranean fruit fly, Ceratitis capitata, for citrus crops in Spain has been threatened by the development of resistance to malathion and lambda-cyhalothrin in recent years. Spinosad is widely used without apparent loss of efficacy. However, a highly resistant strain, JW-100s, has been obtained after laboratory selection. Spinosad resistance in JW-100s has been associated with different mutant alleles of the α6 subunit of the nicotinic acetylcholine receptor (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…The spinosad‐resistant strain JW‐100s, derived from field individuals collected in Xàbia in 2007, has been maintained under regular selection in the laboratory, as previously reported 6 . At the time the experiments were performed, the strain was constituted by individuals homozygous for the Ccα6 3aQ68*‐K352* allele and heterozygous for the Ccα6 3aQ68*‐K352* and Ccα6 3aQ68*Δ3b‐4 alleles 6,20 . The isoline Q68*‐K352* is homozygous for the allele Ccα6 3aQ68*‐K352* and was obtained by isolating it from JW‐100s strain 20 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The spinosad‐resistant strain JW‐100s, derived from field individuals collected in Xàbia in 2007, has been maintained under regular selection in the laboratory, as previously reported 6 . At the time the experiments were performed, the strain was constituted by individuals homozygous for the Ccα6 3aQ68*‐K352* allele and heterozygous for the Ccα6 3aQ68*‐K352* and Ccα6 3aQ68*Δ3b‐4 alleles 6,20 . The isoline Q68*‐K352* is homozygous for the allele Ccα6 3aQ68*‐K352* and was obtained by isolating it from JW‐100s strain 20 …”
Section: Methodsmentioning
confidence: 99%
“…Our previous work determined that the inheritance of spinosad resistance in JW‐100s was autosomic and completely recessive 6 . In addition, we showed that spinosad resistance imposes a fitness cost to resistant individuals compared to susceptible ones, since the resistant Ccα6 3aQ68*‐K352* and Ccα6 3aQ68*Δ3b‐4 alleles were not stable when in competition with the wild‐type allele 20 . Remarkably, we also demonstrated that spinosad resistance could have an impact on the behavior of this species, affecting the ability of males homozygous for the Ccα6 3aQ68*Δ3b‐4 allele to detect the parapheromone trimedlure and to mate in competition experiments 20 .…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations